PENGARUH KUALITAS PRODUK DALAM KEPUTUSAN PEMBELIAN SMARTPHONE XIAOMI (Studi Kasus pada Mahasiswa STIE Nasional Banjarmasin) - Mailiana Mailiana; Masrifani Masrifani; Fitriyadi Ramadhan (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2018)
This study aims to prove the influence of product quality on Xiaomi Smartphone purchasing decisions for students from 2014-2015 Banjarmasin National STIE. The dependent variable in this study is the purchasing decision while the independent variable is the product quality which consists of performance, reliability, features, durability, suitability, and design. The population in this study which was the subject of the study were all students from 2014-2015 who used Xiaomi Smartphone which amounted to 40 people.The results of this study are the variables of performance (X1), reliability (X2), features (X3), endurance (X4), suitability (X5) and design (X6) that have a significant effect on the dependent variable (purchasing decision) because t count greater than t table. While for the calculated F value is 26.521 while the F table with a confidence level of 95% or the real level of 0.05 is 3.988 so it can be concluded that the performance variables (X1), reliability (X2), features (X3), durability (X4), suitability (X5) and design (X6) simultaneously have a significant effect on purchasing decision (Y). Conclusion The study found that 1. Performance variables (X1), reliability (X2), features (X3), endurance (X4), suitability (X5) and design (X6) simultaneously have a significant effect on purchasing decisions (Y). 2. Partially, performance variables (X1), reliability (X2), features (X3), durability (X4), suitability (X5) and design (X6) simultaneously have a significant effect on purchasing decision variables (Y).